Evaluation of Postbiotic Supernatants from Selected Lactic Acid Bacteria Against the Survival of Cronobacter spp. in Infant Foods - Latosa, Rhea Anne (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Microbiology, 2026)
Cronobacter is an opportunistic foodborne pathogen associated with severe neonatal infections such as meningitis, sepsis, and necrotizing enterocolitis. It poses a safety concern in infant nutrition due to its ability to persist in dry environments such as powdered infant formulas (PIF), which are not manufactured to be sterile. Cronobacter can remain viable for extended periods of time in low-moisture conditions and resist heat stress during rehydration, making it difficult to eliminate through standard preparation methods. Cronobacter is also able to tolerate and survive in acidic environments, however, the low pH of the gastric fluid in adults is usually enough to kill the bacteria. Unfortunately, infants have a higher gastric fluid pH, allowing Cronobacter to survive and reach the intestinal tract, increasing the likelihood of systemic infection. The use of postbiotics from lactic acid bacteria (LAB) as prophylactic additions to PIF, offer a promising alternative to traditional antimicrobial strategies. The aim of this study was to evaluate the antimicrobial effects of L. plantarum, L. rhamnosus, L. casei and L. helveticus cell-free supernatants (CFS) against Cronobacter as well as assess their stability under different conditions. To assess the antimicrobial effect of L. plantarum, L. rhamnosus, L. casei and L. helveticus CFS, reconstituted dried baby food was mixed with the autoclaved CFS from a 48 h culture diluted 1:5 (CFS : baby food) from the LAB strains and then inoculated with approx. 1 CFU/10 ml of varying Cronobacter strains. After incubation for 24 h at 37℃, CFS from all four LAB strains displayed an inhibition rate of ≥99% against all the Cronobacter strains tested, showing their potential as postbiotics. L. plantarum, L. rhamnosus, L. casei and L. helveticus CFS (10 mg/ml) were also used as treatments to ready to feed formula inoculated with approx. 5 CFU/10 ml of C. sakazakii ES5. The solution was then put through simulated gastrointestinal conditions with a time frame of 6 h and temperature 37℃, although incubation of the solutions went up to 24 h. It was then determined that, at least in the simulated condition, 10 mg/ml of L. plantarum, L. rhamnosus, L. casei and L. helveticus CFS added to ready to feed infant milk was enough to inhibit C. sakazakii ES5 growth for at least 6 h that it could not be detected when samples of the milk were drip plated onto the Chromogenic Cronobacter Isolation (CCI) agar, no C. sakazakii ES5 colonies could be isolated. C. sakazakii ES5 colonies, however, were isolated from samples taken at t=24, thus the antimicrobial activity of the L. plantarum, L. rhamnosus, L. casei and L. helveticus CFS diminished between t=6 and t=24, and that 10 mg/ml of CFS may have a bacteriostatic effect rather than a bactericidal effect. The initial of pH of the solution L. plantarum, L. rhamnosus, L. casei and L. helveticus CFS are added into also affect the LAB CFS's antimicrobial activity. The MIC for all four LAB CFSs was determined to be 10 mg/ml, however when the CFS pH were altered to 7 and 9, C. sakazakii ES5 growth was not inhibited in L broth despite the increased concentration (25 mg/ml). In cultures where the CFS pH was not altered and CFS that were pH adjusted to 3 and 5, C. sakazakii ES5 showed no growth in the L broth. Likewise, when L. plantarum, L. rhamnosus, L. casei and L. helveticus CFS from a 48 h culture were adjusted to pH 5, 7 and 9, and then mixed into melted L agar at a 1:5 dilution, C. sakazakii ES5 growth was also detected after incubation at 37℃ for 18 h, whereas the unaltered CFS as well as pH 3 adjusted CFS showed no C. sakazakii ES5 growth. This comes to relevance when six dried baby foods from different manufacturers were used to test L. plantarum CFS against C. sakazakii ES5. In four of the dried baby foods, C. sakazakii ES5 could not be detected in treated samples. While it was detected in the other two albeit at lower CFU than its control. The acid buffering capacity of all six dried baby foods were checked, and while the two that allowed C. sakazakii ES5 growth did not have the most acid buffering capacity, it had, however, the highest initial pH at approx. pH 6.25. While L. plantarum, L. rhamnosus, L. casei and L. helveticus CFS have shown potential to be effective postbiotics against Cronobacter, it is important to note that its effects vary between strain and the food matrix.
APPROVED
Keywords: Lactic Acid Bacteria; Postbiotics; Infant foods; Powdered Infant Formula; L. plantarum; Cronobacter; L. rhamnosus; L. helveticus; L. casei